Livelihood Status and Income Determinants of Small-Scale Fishers: Evidence from Three Districts in Raja Ampat - Hendra Sudirman; Yulia Sari; Aldila Mawanti Athira (Agro Ekonomi, 2026)
The small-scale fishermen of Raja Ampat in Southwest Papua Province constitute an economically vulnerable community that is confronted with considerable challenges due to restricted access to essential human, financial, physical, natural, and social capital, which are indispensable for enhancing their economic circumstances. The objective of this study is to evaluate the livelihood status of these fishermen and to analyze the factors that influence their income. The data were gathered from 45 small-scale fishing households across South Waigeo, North Waigeo, and Misool districts and analyzed using the Livelihood Assessment Index and multiple linear regression. The findings indicate that small-scale capture fishermen in Raja Ampat Regency possess a relatively low human capital index, with houses and boats representing their primary physical assets. The availability of land, access to open water, and water resources represent the primary natural capital upon which their livelihoods depend. Despite maintaining robust relationships within the community, their social status in external contexts is relatively low. Their income is derived exclusively from fishing activities. The evaluation results indicate that small-scale capture fishermen in Raja Ampat Regency have low livelihood index values. The principal determinants of income are age, experience, training, catch volume, health issues, and involvement in local institutions. To enhance the financial stability and socioeconomic standing of fishermen, this study proposes the implementation of training programs aimed at augmenting catch volumes and fostering income diversification. Additionally, it recommends measures to facilitate enhanced access to educational and health resources, alongside the cultivation of robust organizational abilities.